2019
DOI: 10.1186/s13048-019-0585-2
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin ameliorates polycystic ovary syndrome through AMP-activated protein kinase

Abstract: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder and regarded as the leading cause of anovulatory infertility. PCOS is characterized by reproductive dysfunction and metabolic disorders. Baicalin (BAL) is one of the most potent bioactive flavonoids isolated from the radix of Scutellaria baicalensis. In the present study, we investigated the potential effects of BAL on PCOS in dehydroepiandrosterone-treated rats. We found that BAL notably reduced the serum levels of free testosterone, total testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…In addition, Cyp11a1 and Fdx1 promoter activity was also enhanced by co-treatments with cAMP as reported for apigenin (2), luteolin (3), and chrysin (1). However, others recently reported that baicalein (4) administration for four weeks reduced serum testosterone and FSH and LH levels following treatments of a rat model for polycystic ovary syndrome (PCOS) [43]. In their study, baicalein (4) instead decreased the expression of StAR, Hsd3b, Cyp11a1, and Cyp19a1 in ovarian tissues.…”
Section: Flavonesmentioning
confidence: 86%
“…In addition, Cyp11a1 and Fdx1 promoter activity was also enhanced by co-treatments with cAMP as reported for apigenin (2), luteolin (3), and chrysin (1). However, others recently reported that baicalein (4) administration for four weeks reduced serum testosterone and FSH and LH levels following treatments of a rat model for polycystic ovary syndrome (PCOS) [43]. In their study, baicalein (4) instead decreased the expression of StAR, Hsd3b, Cyp11a1, and Cyp19a1 in ovarian tissues.…”
Section: Flavonesmentioning
confidence: 86%
“…Natural compounds have high potential in PCOS therapy. Flavonoid baicalin (isolated from Scutellaria baicalensis ) has been shown to decrease levels of testosterone, LH, progesterone and estradiol, and several proinflammatory cytokines (IL-1β, IL-18 and TNFα) and normalise IR in PCOS-induced rats [ 96 ]. Similarly, flavonoids recovered from Nervilia Fordii decrease the levels of IL-6 and hormones LH, testosterone and insulin and increase the serum level of FSH [ 97 ].…”
Section: Pcos Treatments: Classical and Modern Mitochondria–oriented Approachesmentioning
confidence: 99%
“…In human granulosa cells, through AMPK-dependent mechanisms, MF suppresses the tumor necrosis factor-α (TNF-α)-induced production of pro-inflammatory cytokines, interleukin-8 and chemokine CXCL1/GROα [ 303 ]. The other AMPK activators, such as AICAR and Baicalin, also reduce TNF-α- and chemokine-mediated inflammatory responses in ovarian cells [ 303 , 304 ]. In PCOS ovarian cells, the mechanism of MF suppressive effect on the TNF-α-induced cascades includes a decrease in the gene expression of TNF-α [ 217 ].…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%